2023
DOI: 10.3390/ma16113964
|View full text |Cite
|
Sign up to set email alerts
|

Advancement of Nonwoven Fabrics in Personal Protective Equipment

Abstract: While nonwoven fabrics have existed for several decades, their usage in personal protective equipment (PPE) has been met with a rapid surge of demands, in part due to the recent COVID-19 pandemic. This review aims to critically examine the current state of nonwoven PPE fabrics by exploring (i) the material constituents and processing steps to produce fibers and bond them, and (ii) how each fabric layer is integrated into a textile, and how the assembled textiles are used as PPE. Firstly, filament fibers are ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 91 publications
0
10
0
Order By: Relevance
“…Other researchers also confirmed that the permeability properties of fabrics are mainly related to the pore size and porosity of the fibres [ 3 ]. The permeability properties also increase with a smaller surface area of the nonwoven fabric structure and the thickest fibres, as well as with the number of layers in the nonwoven fabric [ 4 , 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers also confirmed that the permeability properties of fabrics are mainly related to the pore size and porosity of the fibres [ 3 ]. The permeability properties also increase with a smaller surface area of the nonwoven fabric structure and the thickest fibres, as well as with the number of layers in the nonwoven fabric [ 4 , 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the micro air pockets formed in the treated and commercial samples are similar, the thermal performances of both samples were quite comparable. The thickness plays a vital role in achieving the desired thermal insulation [70][71][72].…”
Section: Thermal Resistancementioning
confidence: 99%
“…Fibre blend plays a crucial role in determining the mechanical properties of needle-punched nonwovens [5][6][7]. By carefully selecting and blending different types of fibres, it is possible to enhance specific properties such as tensile strength, tear strength, burst strength, abrasion resistance, and flexibility, thus tailoring the nonwoven fabric for various applications and performance requirements [1,4,[8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%